Features of the Digital Filters Implementation on STM32 Microcontrollers - Zubkov, O.; Svyd, I.; Vorgul, O. (My University, 2021)
The purpose of this work is to study the efficiency of compilation of digital filters software implementation for STM32 microcontrollers. The research included: the stage of filter synthesis according to its amplitude-frequency characteristic and order, analysis of the signal at the filter output for various types of the program code optimization. As a result of the research, practical recommendations were given for choosing a compiler and the level of optimization in devices containing digital filters.
Keywords: compiler; microcontroller; optimization; low pass filter; frequency response